Development of Swimming Learning Video Media Based on Camtasia for Class XI Students at Smk 17 Parakan, Temanggung - Muhammad Akbar Alrasyid; Haryono Haryono; Titi Prihatin; Tri Suminar; Kustiono Kustiono (Universitas Negeri Semarang, 2021)
This study analyzes the results of Camtasia-Based Swimming Learning Media Development for Class xi students at SMK 17 Parakan Temanggung. Products are packaged in videos, and products can be used independently using Android online by students. This learning media was developed using the Research and Development method of the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Applications were assessed by one material expert, one media expert, and two teachers. They administered a questionnaire to 6 students (2 high-ability students, two medium-ability students, and two low- ability students). The validity of the media expert showed that at 3.77, it could be classified as